INTERNALISASI NILAI-NILAI MODERASI MELALUI KITAB AT-TAḤLIYYAH (STUDI KASUS DI MADRASAH DINIYAH HM AL-MAHRUSIYAH) - Muhammad Ullin Nuha; Reza Ahmad Zahid; Abbas Sofwan M.F. (Jurnal Studi Pesantren, 2026)
This study explores the process of internalizing the values of religious moderation through the learning of the At-Taḥliyyah book at Madrasah Diniyah HM Al-Mahrusiyah Lirboyo Kediri as part of character formation for moderate-minded students. The increasing trend of exclusivism and intolerance among certain groups forms the background of this research. As traditional Islamic educational institutions, pesantrens play a strategic role in instilling balance and tolerance through cultural and exemplary approaches. This research adopts a qualitative descriptive method with data collected through observation, in-depth interviews, and documentation of the At-Taḥliyyah  learning process. The data were analyzed using the Miles and Huberman model, including reduction, presentation, and conclusion drawing. The results reveal that the internalization of moderation values occurs through three main stages: value transformation, value transaction, and value transinternalization. Through these stages, students not only understand moderation cognitively but also apply it in social behavior that reflects tawassuṭh (moderation), i‘tidāl (justice), tasāmuh (tolerance), syūrā (consultation), iṣlāḥ (reform), and muwāṭanah (patriotism). This study concludes that the At-Taḥliyyah book serves as an effective educational medium for strengthening student character in line with national values, humanism, and the Ministry of Religious Affairs’ vision of religious moderation.